Website Penyampaian Keluhan Penumpang Sebagai Media Pelacak Kerusakan, Kelayakan, dan Kenyamanan Fasilitas di Bandar Udara Secara Efektif dan Real Time - Arnas, Yenni; Novi Mediaswati, Cristina; Diana Sari, Dita; Arrahma, Khuzamah; Rifa Nashardin, M; Julio Rumkorem, Sefanya (Jurnal Teknik Mekanikal Bandar Udara, 2023)
The rapid development and advancement of technology today into human activities become lighter and easier. But the ease can be felt when a person can be literate about technology and make maximum use of technology. This research was conducted in order to utilize and implement technological developments to facilitate the work to be more effective. This study was conducted in the form of making software-based technology or digital applications that are installed on mobile computing devices. This Software will assist an aircraft passenger in submitting complaints such as damage or discomfort conditions related to facilities at the airport in real time. The main target of this study is passenger aircraft, because the comfort of passengers is a representative form of the quality of an airport.